Assessment of permeability and injection depth at the Atasu dam site (Turkey) based on experimental and numerical analyses - Gurocak, Zulfu; Alemdag, Selcuk (Springer Heidelberg, 2012)
This study was performed in order to evaluate the permeability of the basalts and pyroclastics and the maximum depth of grout injection at the Atasu dam site, Turkey, using the equations of Kiraly and Hoek and Bray based on values obtained from Lugeon tests. In order to evaluate maximum discharge values and depth of injection, seepage analyses were performed using the finite element technique for each 10 m up to 100 m. The results indicate that to establish an impermeable zone at the dam site, the depth of injection should be taken as 50 m for the left and right slopes and 40 m for the river bed.
Keywords: Atasu dam; Permeability; Lugeon test; Finite element method; Seepage analysis